2016
DOI: 10.29311/ndtps.v0i11.567
|View full text |Cite
|
Sign up to set email alerts
|

The opportunities and challenges for employability-related support in STEM degrees

Abstract: This research explores the opportunities and challenges for incorporating employability-related support into STEM (Sciences; Technology; Engineering; Mathematics) degree programmes, based in part on recent research (O’Leary, 2016a) outlining that significant variations in employability-related support exist across the STEM disciplines. These issues were highlighted at a recent conference on STEM pedagogy (O’Leary, 2016b) and this paper explores them in more depth. While O’Leary (2016a) finds that Engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
2
1
0
1
Order By: Relevance
“…Furthermore, this study found that generic skills were a strong predictor of employability, which is consistent with previous studies [77,79]. Other studies have demonstrated that to gain generic skills, students must constantly practice communicating with others and participating in group activities [80].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this study found that generic skills were a strong predictor of employability, which is consistent with previous studies [77,79]. Other studies have demonstrated that to gain generic skills, students must constantly practice communicating with others and participating in group activities [80].…”
Section: Discussionsupporting
confidence: 91%
“…These results confirmed that graduates who secure employment in professions that make good use of the skills and information acquired during their university studies are often successful in the graduate labor market. Furthermore, this study revealed that working experience was a significant predictor of the employability, which is consistent with the previous research of O'Leary [77]. Though the experiences of the graduates in this study were found to vary, they all indicated a significant need for employability-related support to be included in undergraduate degree programs.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that in this university students recognise and value the multiple types of learning experiences offered to them. This matters because teaching methods which encourage complex learning enhances employability (Nicol, 2010;Knight & Yorke, 2003), an expectation of higher education (O'Leary, 2016;Swingler et al, 2016;Blackmore et al, 2016). Students need to understand how important graduate attributes are, acknowledge what skills they are developing through different assignments, activities and tasks, and why it is important that they can demonstrate them (Green et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Во многих странах мира большая доля выпускников трудоустраивается не по профилю образования, что приводит к нехватке специалистов в определенных отраслях и ставит под сомнение эффективность инвестиций государства в образование. Все это объясняет большое количество исследований по всему миру [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] в области трудоустройства выпускников. В России, в частности, также предпринимались серьезные попытки анализа качества трудоустройства выпускников вузов страны и их результаты легко доступны [17][18][19][20].…”
Section: Introductionunclassified